2018
DOI: 10.1371/journal.pone.0192051
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and aggregation by the opportunistic pathogen Cutibacterium (Propionibacterium) acnes

Abstract: Cutibacterium (Propionibacterium) acnes, considered a part of the skin microbiota, is one of the most commonly isolated anaerobic bacteria from medical implants in contact with plasma. However, the precise interaction of C. acnes with blood cells and plasma proteins has not been fully elucidated. Herein, we have investigated the molecular interaction of C. acnes with platelets and plasma proteins. We report that the ability of C. acnes to aggregate platelets is dependent on phylotype, with a significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Cutibacterium acnes is one of predominant components of the skin microbiome (Petersson et al, 2018). It is suspected to be involved in acne formation, but its role remains unclear (Tomida et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutibacterium acnes is one of predominant components of the skin microbiome (Petersson et al, 2018). It is suspected to be involved in acne formation, but its role remains unclear (Tomida et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Both S. aureus and C. acnes are opportunistic pathogens, and can sometimes be at the origin of skin disorders. In this way, C. acnes is considered to be one of the causes of acne vulgaris (Fitz-Gibbon et al, 2013; Achermann et al, 2014; Petersson et al, 2018). In parallel, it has been shown that C. acnes can be a cause of complications after operations and the setup of prosthetic implants (Howlin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other fibrinogen-binding proteins from Gram-positive bacteria, DsA1 may be involved in adaptive capacity, promoting the clumping action with fibrinogen and enabling the bacteria to colonize and tolerate the PSU environment [ 160 ]. Indeed, studies of plasma proteins have shown that fibrinogen adheres to the surface of C. acnes and mediates platelet aggregation [ 161 ]. DsA1 therefore appears to be an important surface protein expressed by C. acnes and further investigations of its role as a virulence factor are required.…”
Section: C Acnes Virulence Factorsmentioning
confidence: 99%
“…When platelets were challenged with bacteria, a distinct lag phase preceded platelet aggregation (Kerrigan et al., 2007). This delay in aggregation was affected by the platelet to bacteria ratio, where increasing bacterial concentration reduced lag times (Petersson et al., 2018; Rasmussen et al., 2010). Bacterial interaction with platelets can occur via two main mechanisms: direct and indirect.…”
Section: Discussionmentioning
confidence: 99%